The creep tapes. Season one [videorecording (Blu-Ray)] - Duplass, Mark; Brice, Patrick (Director); Luciano, Mike; Nordstrom, David (Shudder, 2025)
The Creep Tapes is a collection of video tapes from the secret vault of the world's deadliest and most socially uncomfortable serial killer.